Parental education accounts for variability in the IQs of probands with Down syndrome: A longitudinal study. Issue 1 (21st November 2017) - Evans, David W.; Uljarević, Mirko
Abstract : Recent work has demonstrated that variability in probands' phenotypes, including physical features, cognitive abilities, social functioning, and other developmental domains, is influenced by parental traits. Here we examine the role of parental education as a factor contributing to the variability of intelligence quotient (IQ) of offspring with trisomy 21. Participants were 43 probands with trisomy 21, aged 4–21 years of age, and their parents. Data were collected on parental education, and a bi‐parental mean education score (BMES) was calculated. Probands' cognitive abilities were assessed by the Stanford‐Binet 4th edition at baseline (T1), and again 24 months later (T2). Probands were placed into one of two age groups: 4–12 years and 13–21 years. Results indicated higher parent‐proband correlations in Age Group 2 (mean r = .47) relative to Age Group 1 (mean r = .33) and increasing parent‐proband correlations across time, with mean correlations of Age Group 1, T1: r = .26, T2: 39; Age Group 2 T1: r = .49, T2: r = 46. Despite the expected IQ deficits observed in trisomy 21 probands, parental education may still contribute to the variability of probands' cognitive abilities. These findings are consistent with the literature noting increasing heritability of IQ with development.